2005
DOI: 10.1677/joe.1.06052
|View full text |Cite
|
Sign up to set email alerts
|

Bradykinin stimulates cell proliferation through an extracellular-regulated kinase 1 and 2-dependent mechanism in breast cancer cells in primary culture

Abstract: We have previously reported that bradykinin (BK) represents an influential mitogenic agent in normal breast glandular tissue. We here investigated the mitogenic effects and the signalling pathways of BK in primary cultured human epithelial breast cells obtained from a tumour and from the histologically proven non-malignant tissue adjacent to the tumour. BK provoked cell proliferation, increase in cytosolic calcium, activation of protein kinase C (PKC)-, -, -, -´and -and phosphorylation of the extracellular-reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 50 publications
1
31
0
Order By: Relevance
“…PGE2 and BK have been implicated in the growth of colon and breast carcinoma, respectively (7,8). Here, we have shown that GPCR ligands PGE2 and BK induce mitogenic effects in HNSCC cells.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…PGE2 and BK have been implicated in the growth of colon and breast carcinoma, respectively (7,8). Here, we have shown that GPCR ligands PGE2 and BK induce mitogenic effects in HNSCC cells.…”
Section: Discussionmentioning
confidence: 70%
“…4,6). GPCR ligands prostaglandin E2 (PGE2) and bradykinin (BK) are inflammatory molecules that have been previously reported to contribute to the proliferation of colon and breast cancer cells, respectively (7,8). PGE2 has been reported to activate EGFR in tumors, including colon cancer, by activating other molecules, including Src and matrix metalloproteinases (MMP; refs.…”
Section: Introductionmentioning
confidence: 99%
“…There Table 5 Phosphoric ester hydrolase activity CTDSPL2, CTDSPL, PON2, PFKFB1, PFKFB2, IMPA2, INPP5B, NT5C1B, NT5E, DLG7, CTDP1, CILP, PPAP2B, PPAP2C, DLG1, LCK, PPM1A, PPM1H, RGS12, TIAM1, BAG4, MS4A1, DCLK1, BRAF, STYX Table 5 that are implicated to play roles in the progression of breast cancer or other cancers, including BDKRB2 (Greco et al, 2005), PLCB1 (Naor, 2009), PLD1 (Eisen and Brown, 2002), GPLD1 (Derevianko et al, 1996;Williams et al, 2001), EXO1 (Naderi et al, 2007), ANG (Campo et al, 2005), ISG20/HEM45 (Pentecost, 1998), AZGP1/ZAG (Hassan et al, 2009), ZKSCAN1 (Pennanen et al, 2009), REXO2 (Flanagan et al, 2009), CTDSPL (Murabito et al, 2007), NT5E (Zhou et al, 2007), DLG1 (Fuja et al, 2004), PPM1A (Lin et al, 2006), TIAM1 (Lane et al, 2008), BAG4 (Yang et al, 2006), BRAF (Hollestelle, et al, 2007), CLDN4 (Kulka et al, 2009), F3/TF (Amirkhosravi et al, 1998), FZD1 (Benhaj et al, 2006), NGFR (Reis-Filho et al, 2006), LEFR , RAC1 , PLXNB1 (Rody et al, 2007), IGHG1 (Kabbage et al, 2008), IGHG3 (Bin Amer et al, 2008), TLR3 (Salaun et al, 2006), FBN1 , DUSP4 (Venter et al, 2005), PTPN3 (Wang et al, 2004), CDKN3/KAP (Lee et al, 2000), and etc.…”
Section: Resultsmentioning
confidence: 99%
“…The expression of BK receptors has been demonstrated in clinical speciments of adenocarcinoma, squamous carcinoma, lymphoma, hepatoma and carcinoid, and in experimental mouse sarcoma 180 and colon adenocarcinoma 38 (Wu et al, 2002), in small cell and non-small cell carcinomas of the lung (Chee et al, 2008), and in oesophageal squamous cell carcinoma (Dlamini et al, 2005). The mitogenic effects of BK have been reported in primary cultured epithelial breast cancer cells and in MCF-7 breast cancer cell line, where BK stimulated cell proliferation through ERK activation (Greco et al, 2005;Greco et al, 2006). Because there were limited studies on the role of BK in renal cell carcinomas, we have chosen to use A498 cells, a transformed cell line derived from primary undifferentiated kidney carcinoma (Giard et al, 1973), which represents a widely used model for studying of renal carcinomas.…”
Section: Nhe1 Regulates Erk Activity In Bradykinin-activated Renal Camentioning
confidence: 94%